Urinary complications and risk factors in symptomatic multiple sclerosis patients. Study of a cohort of 328 patients. Issue 1 (23rd September 2013) - Castel‐Lacanal, Evelyne; Gamé, Xavier; Clanet, Michel; Gasq, David; De Boissezon, Xavier; Guillotreau, Julien; Bourg, Véronique; Viala, Frédérique; Rischmann, Pascal; Marque, Philippe
Abstract Aims Lower urinary tract dysfunctions (LUTD) are very common in Multiple Sclerosis (MS), have a significant social impact, while the organic impact is discussed. We studied urinary complications and their risk factors in our cohort of MS patients, in order to improve the management of LUTD in MS. Methods Between 2004 and 2009, all patients affected by MS and managed for LUTD were included in a retrospective study. We studied the epidemiological data (age, gender), the clinical data (duration of MS, EDSS score, progression of MS) and the paraclinical data (urinary creatinine clearance, urine culture, urinary tract ultrasonography and in some cases urodynamic assessment and cystography). We then identified the urinary complications and their risk factors. Results Three hundred twenty eight patients, mean age 49.9 ± 12.3 years, with a MS for 14.3 ± 10 years on average and with a median EDSS score equal to 6 (1–9), were managed for LUTD. One hundred seventy eight (54%) patients developed one or more urinary complications. We identified duration of MS greater than 8.5 years and an EDSS above 7 as risk factors. Conclusion Urinary complications are common in symptomatic MS, these results imply screening and specialized care to limit the impact on the quality of life but also to prevent urinary complications. Neurourol. Urodynam. 34:32–36, 2015. © 2013 Wiley Periodicals, Inc.